Polynitro Containing Energetic Materials based on Carbonyldiisocyanate and 2, 2‐Dinitropropane‐1, 3‐diol12. Issue 1 (11th December 2013) - Klapötke, Thomas M.; Krumm, Burkhard; Rest, Sebastian F.; Sućeska, Muhamed
Abstract New polynitro compounds containing a carbonyl biscarbamate moiety derived from the precursor carbonyldiisocyanate were synthesized. In addition, 2, 2‐dinitropropane‐1, 3‐diyl bis(2, 2, 2‐trinitroethylcarbamate) and 2, 2‐dinitropropane‐1, 3‐diyl bis(2, 2, 2‐trinitroethyl) dicarbonate, were synthesized using 2, 2‐dinitropropane‐1, 3‐diol as starting material. The compounds were characterized by using the analytical methods, single‐crystal X‐ray diffraction, vibrational spectroscopy (IR and Raman), multinuclear NMR spectroscopy, elemental analysis, and mass spectrometry. The thermal behavior was investigated with DSC measurements. The suitability of the compounds as potential oxidizers in energetic formulations was determined. The heats of formation of the compounds were calculated with GAUSSIAN 09. The detonation parameters such as the detonation pressure, velocity, energy, and temperature were computed using the EXPLO5 code. For a secure handling of the materials, the sensitivity towards impact, friction, and electrical discharge was tested using the BAM drop hammer, BAM friction tester as well as a small‐scale electrical discharge device, respectively.